Phase I/II trial of dendritic cell-based active cellular immunotherapy with DCVAC/PCa in patients with rising PSA after primary prostatectomy or salvage radiotherapy for the treatment of prostate cancer - Fucikova, Jitka; Podrazil, Michal; Jarolim, Ladislav; Bilkova, Pavla; Hensler, Michal; Becht, Etienne; Gasova, Zdenka; Klouckova, Jana; Kayserova, Jana; Horvath, Rudolf; Fialova, Anna; Vavrova, Katerina; et al. (Cancer immunology and immunotherapy, 2018)
OBJECTIVE: Immunotherapy of cancer has the potential to be effective mostly in patients with a low tumour burden. Rising PSA (prostate-specific antigen) levels in patients with prostate cancer represents such a situation. We performed the present clinical study with dendritic cell (DC)-based immunotherapy in this patient population. MATERIALS AND METHODS: The single-arm phase I/II trial registered as EudraCT 2009-017259-91 involved 27 patients with rising PSA levels. The study medication consisted of autologous DCs pulsed with the killed LNCaP cell line (DCVAC/PCa). Twelve patients with a favourable PSA response continued with the second cycle of immunotherapy. The primary and secondary objectives of the study were to assess the safety and determine the PSA doubling time (PSADT), respectively. RESULTS: No significant side effects were recorded. The median PSADT in all treated patients increased from 5.67 months prior to immunotherapy to 18.85 months after 12 doses (p < 0.0018). Twelve patients who continued immunotherapy with the second cycle had a median PSADT of 58 months that remained stable after the second cycle. In the peripheral blood, specific PSA-reacting T lymphocytes were increased significantly already after the fourth dose, and a stable frequency was detected throughout the remainder of DCVAC/PCa treatment. Long-term immunotherapy of prostate cancer patients experiencing early signs of PSA recurrence using DCVAC/PCa was safe, induced an immune response and led to the significant prolongation of PSADT. Long-term follow-up may show whether the changes in PSADT might improve the clinical outcome in patients with biochemical recurrence of the prostate cancer.
Keywords: Radiotherapy; lidé; tumor burden; výsledek terapie; Middle Aged; imunoterapie; prostatický specifický antigen; prostatektomie; Prostatectomy; Humans; Tumor Burden; Prostatic Neoplasms; Gene Expression Regulation, Neoplastic; T-lymfocyty; lidé středního věku; Immunotherapy; T-Lymphocytes; mužské pohlaví; Prostate-Specific Antigen; nádory prostaty; Lymphocyte Count; Dendritic Cells; počet lymfocytů; radioterapie; Treatment Outcome; regulace genové exprese u nádorů; Male; Aged; dendritické buňky; senioři